Pengaruh Waktu Treatment Serat terhadap Sifat Mekanik Komposit Serat Tapis Kelapa - Ngakan Putu Gede Suardana; Ni Made Dwidiani (Jurnal Teknik Industri, 2007)
Coconut tapis fiber is one of the natural fiber for use composites on account of its characteristic such as a high strength to weight ratio, resistance to corrosion, resistance to wear, good finishing surface, no health risk and easy availability. This research was conducted to study tensile strength and flexural strength of coconut tapis fiber reinforced composite with variable of fiber treatment in NaOH for 2, 4, and 6 hours. This research used coconut tapis fiber with 0.04 -1 mm diameter and 10 mm length, resin unsaturated polyester type Yukalac 157 BQTN-EX as its matrix, and metil etil keton peroxide 1% as its hardener. The fiber was treted in NaOH for 2, 4, and 6 hours, afterward rinsed and dried, respectively. The composite was made using press hand lay-up technique with post curing 2 hours at temperature of 620C. Tensile and flexure test specimen were made based on ASTM D3039 and ASTM D 790-03 standard accordingly. The result shows that tensile strength decrease with increasing treatment in NaOH. The highest tensile strength was achieved by 2 hours treatment in NaOH at 58.8 MPa. The highest tensile strain was achieved by 2 hours treatment NaOH at 1.30%. The highest tensile modulus of elasticity was achieved by 6 hours treatment in NaOH at 5.07 GPa. In agreement with tensile strength, flexural strength also decreased with increasing treatment in NaOH. The highest flexural strength was achieved by 2 hours treatment in NaOH at 125.98 MPa, and the highest flexural strain was achieved by 2 hours treatment in NaOH at 1.35%. The highest flexural modulus of elasticity was achieved by 6 hours treatment in NaOH at 13.55GPa.